The LDL1/2-HDA6 Histone Modification Complex Interacts With TOC1 and Regulates the Core Circadian Clock Components in Arabidopsis - Hung, Fu-Yu; Chen, Fang-Fang; Li, Chenlong; Chen, Chen; Chen, Jian-Hao; Cui, Yuhai; Wu, Keqiang (Frontiers in Plant Science, 2019)
In Arabidopsis, the circadian rhythm is associated with multiple important biological processes and maintained by multiple interconnected loops that generate robust rhythms. The circadian clock central loop is a negative feedback loop composed of the the core circadian clock components. TOC1 (TIMING OF CAB EXPRESSION 1) is highly expressed in the middle of the day and negatively regulates the expression of CCA1 (CIRCADIAN CLOCK ASSOCIATED 1)/ LHY (LATE ELONGATED HYPOCOTYL). CCA1/LHY also binds to the promoter of TOC1 and represses the TOC1 expression. Our recent research revealed that the histone modification complex comprising of LYSINE-SPECIFIC DEMETHYLASE 1 (LSD1)-LIKE 1/2(LDL1/2) and HISTONE DEACETYLASE 6 (HDA6) can be recruited by CCA1/LHY to repress TOC1 expression. In this study, we found that HDA6, LDL1 and LDL2 can interact with TOC1, and the LDL1/2-HDA6 complex is associate with TOC1 to repress the CCA1/LHY expression. Furthermore, LDL1/2-HDA6 and TOC1 co-target a subset of genes involved in the circadian rhythm. Collectively, our results indicate that the LDL1/2-HDA6 histone modification complex is important for the regulation of the core circadian clock components.